The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.6018/eglobal.16.2.239681
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de impacto de la crisis económica sobre el síndrome de Burnout y resiliencia en el personal de enfermería

Abstract: Este proyecto de  investigación pretende analizar las condiciones de trabajo, las variables individuales y de salud que están relacionadas con el desarrollo del síndrome de burnout, así como el potencial efecto de la “entereza” o “personalidad resistente”,  presente en nuestro ámbito de trabajo, todo esto en el contexto de crisis económica en la que nos encontramos en la actualidad. Partiendo de este análisis, se podrían plantear estrategias de cambio con el fin de mejorar la satisfacción laboral y disminuir l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 15 publications
2
3
0
10
Order By: Relevance
“…With respect to Spain in particular, over the last decade, adjustments made to the National Health System as a result of the economic crisis have left nursing professionals with a growing sense of worsening working conditions. This translates into understaffing, work overload, decreased time for direct patient care, increased working hours, lack of solidarity with healthcare professionals on the part of managers and decreased salaries [25]. In addition, studies on PQoL have suggested that Spanish nurses have moderate to high levels of compassion fatigue and burnout [26].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to Spain in particular, over the last decade, adjustments made to the National Health System as a result of the economic crisis have left nursing professionals with a growing sense of worsening working conditions. This translates into understaffing, work overload, decreased time for direct patient care, increased working hours, lack of solidarity with healthcare professionals on the part of managers and decreased salaries [25]. In addition, studies on PQoL have suggested that Spanish nurses have moderate to high levels of compassion fatigue and burnout [26].…”
Section: Introductionmentioning
confidence: 99%
“…No que tange ao sentimento de insatisfação profissional, sabe-se que este aumenta as chances de atitudes de segurança deficientes (15) . No presente estudo, essa dimensão apresentou nível baixo na maioria das respostas, indicando que os profissionais não se sentiam reconhecidos pelo trabalho que desempenhavam, podendo gerar desmotivação e tristeza no exercício profissional.…”
Section: Discussionunclassified
“…As repercussões da crise econômica sobre a saúde da população, em geral, influenciam em aumento na maioria das doenças, especialmente problemas de saúde mental, bem como aumento do uso de drogas, trauma e suicídio. A despersonificação se correlacionou diretamente com a diminuição do salário, em estudo espanhol (Sánchez, Martínez, Lázaro Sahuquillo, Román & Cantó, 2017). Observam-se, no cotidiano, as dificuldades encontradas pelos profissionais de saúde, de forma geral, no cenário atual no estado do Rio de Janeiro o que corrobora as constatações dos autores supracitados, o que se potencializa com a dificuldade de enfrentamento coletivo.…”
Section: Fatores Relacionados à Gênese Do Burnout E Implicaçõesunclassified
“…Pesquisas no Brasil, Estados Unidos e Espanha revelaram impacto do burnout na qualidade do sono (Sánchez, Martínez, Lázaro Sahuquillo, Román & Cantó, 2017;Andolhe, Barbosa, Oliveira, Costa & Padilha, 2015;Bamonti et al, 2017). A privação do sono provoca diversos distúrbios, sendo os principais: gastrointestinais; cardiovasculares; cognitivos; flutuações de humor; comprometimento do desempenho das atividades; pessoais; sociais e do trabalho, pois diminui a capacidade de concentração e atenção.…”
Section: Riscos à Saúde Mental E Qualidade De Vida Do Trabalhadorunclassified
See 1 more Smart Citation